New studies in dogmatics : Sanctification - Allen, Michael (Zondervan, 2017)
Sanctification—the act or process of becoming holy—is one of the gifts of the gospel of Jesus Christ, but it's often misunderstood by the modern church. Sanctification offers a Christ-centered and clear account of the doctrine by viewing it within its wider biblical and historical context.